Effect of Feeding Button Weed Silage on the Growth Performance of (Tenyivo×Hampshire) Upgraded Tenyivo Pig - Talilemba; Rutsa, M. Catherine; Zuyie, R.; Singh, Rajan (International Journal of Livestock Research, 2023)
The present study entitled “Effect of feeding Button weed silage on the growth performance of upgraded Tenyivo pig” was carried out to study the effect of feeding button weed (Borreriaarticularis) silage on twenty upgraded Tenyivo pigs. The experimental animals were divided into two groups of ten animals each. The experimental diet consisted of T1– 100% conventional feeds and T2– 80% conventional feeds + 20% button weed silage. The animals were reared under a standard management housing system. The recorded average body weight at ten weeks for T1 and T2 was 10.97±0.75kg and 10.46±0.71kg, respectively with no significant difference (P≥0.05). The average daily gain (ADG) for T1 and T2 was 171.53g and 149.99g respectively. Statistical analysis (t-test) showed no significant difference (P≥0.05) in the second, third, fourth, sixth, seventh, eighth, and tenth weeks however, a significant difference (P≤0.05) was observed in the first, fifth, and ninth weeks. Feed consumption was significantly higher in T1 as compared to T2. The average feed conversion efficiency (FCE) recorded in T1 and T2 was 2.39 kg and 2.54 kg respectively, with no significant difference (P≥0.05). The benefit-cost ratio in the group replaced by 20% button weed silage was 1:1.28 with net returns of ₹ 1146.35 and ₹ 1017.28 in the respective treatment groups.